Wan Azizah continues Anwar's hindered agenda in Kajang - Borneo Post, (KK) (Borneo Post (KK), 2014)
KUALA LUMPUR: The selection of Parti Keadilan Rakyat (PKR) president Datin Seri Wan Azizah Wan Ismail as the party's candidate for the by-election for the Kajang State Legislative Assembly seat is seen by political analysts as an effort to continue the political agenda of her husband that was hindered.